A novel long-stroke fast tool servo system with counterbalance and its application to the ultra-precision machining of microstructured surfaces. (1st July 2022) - Gong, Zheng; Huo, Dehong; Niu, Zengyuan; Chen, Wanqun; Cheng, Kai
Highlights: A novel long stroke fast tool servo system with counterbalance was designed. A hybrid control algorithm was developed and tested on the system. Performances of the FTS system were tested through simulations and machining experiments. System vibration and following errors were significantly decreased by the counterbalance design. Abstract: This paper presents a novel long-stroke fast tool servo (FTS) system with counterbalance and its application to the diamond machining of microstructured surfaces. The FTS system is driven by a voice coil motor and guided by air bearings. A hybrid control algorithm which combines PID control, sliding mode control and feed-forward control was specifically designed for the system and ensures that it has less than 1% tracking error and achieves ± 1 mm stroke and 105 Hz bandwidth. The counterbalance is achieved by the symmetric arrangement of two of the same FTS systems. System vibration decreased significantly from ± 3 μm to ± 0.145 μm when the counterbalance was working. Machining experiments were conducted using the FTS system on a diamond turning machine. A microstructured surface simulation model was built and information about the workpiece surface tested and collected. When the counterbalance was working, error in the machine axes decreased from micron-level to nano-level and the surface roughness of the microstructured surface was also reduced. The system achieves ± 1 mm (±0.5 mm) stroke at 30 Hz (40 Hz) with 0.35% (0.68%) tracking error during machining processes, and the depth error of the machined microstructured surface was measured at 1.4% (2.3%).